Diabetic Foot Ulcers: Surgical Characteristics, Treatment Modalities and Short-Term Treatment Outcomes at a Tertiary Hospital in South-Western Uganda - Sikhondze MM; Twesigye D; Odongo CN; Mutiibwa D; Tayebwa E; Tibaijuka L; Ayana SD; Cabrera Dreque C (Open Access Surgery, 2022)
Mvuyo Maqhawe Sikhondze,1 Deus Twesigye,2 Charles Newton Odongo,3 David Mutiibwa,1 Edson Tayebwa,1 Leevan Tibaijuka,4 Samuel D Ayana,5 Carlos Cabrera Dreque1 1Department of Surgery, Mbarara University of Science and Technology, Faculty of Medicine, Mbarara City, South-western Uganda, Uganda; 2Department of Surgery, Mbarara Regional Referral Hospital, Mbarara City, South-western Uganda, Uganda; 3Department of Anatomy, Faculty of Medicine, Soroti University, Soroti, Uganda; 4Department of Obstetrics and Gynaecology, Mbarara University of Science and Technology, Mbarara City, South-western Uganda, Uganda; 5Department of Surgery, Hlathikhulu Hospital, Hlathikhulu, EswatiniCorrespondence: Mvuyo Maqhawe Sikhondze, Department of Surgery, Mbarara University of Science and Technology, P.O. Box 1410, Mbarara City, Uganda, Tel +268 7996 6776, Email maqhawesikhondze@yahoo.co.ukBackground: Diabetic foot ulcers (DFUs) are a prevalent and serious consequence of poorly controlled diabetes. Hospitalizations are frequent among DFU patients, and these patients are at risk of lower extremity amputations (LEA). Uganda has few studies detailing DFUs and their management. We described the surgical characteristics, treatment modalities and short-term treatment outcomes of DFUs at Mbarara Regional Referral Hospital, in southwestern Uganda.Methods: A prospective cohort study involving 62 patients with DFUs was conducted from February 2021 to September 2021. We captured socio-demographic data, surgical characteristics, treatment and treatment outcomes of DFUs over a 5-week follow-up period, through an interviewer-administered structured questionnaire. Descriptive statistics were used at analysis.Results: The mean age of participants was 57.0 ± 12.27 years, comprising 35 (56.5%) females. Majority had diabetes mellitus (DM) for more than 10 years, predominantly type 2 (93.5%), and 33.9% with very poor glycaemic control (HBA1c> 9.5%). Most ulcers involved the toes (27.4%), with 80.7% being large (> 3 cm2). Severe DFUs (Wagner grade 3– 5) were seen in 66.2% of patients. Clinically infected ulcers mainly had Pseudomonas spp cultured. Arterial occlusion was detected in 35.5% through lower extremity Doppler ultrasonography. Initial surgical interventions were surgical debridement and LEA performed in 50.0% and 46.8%, respectively. Eight (42.1%) patients suffered surgical site infection, while 26.3% had persistent gangrene after initial surgery. Revision surgery was performed in 25.8% of the participants. Mortality rate was 1.6%, and mean length of hospital stay was 17.0 ± 11.1 days.Conclusion: More than half of the patients had advanced DFUs (Wagner grades 3– 5). Poor glycemic control and late presentation were common. Lower extremity amputation was a common initial treatment modality for DFUs. Routine lower extremity Doppler ultrasonography is recommended to assess peripheral arterial disease for DFU patients. Wound swabbing for culture and sensitivity testing is encouraged for appropriate antibiotic coverage.Keywords: diabetic foot ulcer, Wagner classification, Uganda